Communicating Awareness About COVID-19 Through Songs: An Example From Ghana - Rachel G. A. Thompson; Jerry John Nutor; Julene K. Johnson (Frontiers Media S.A., 2021)
Research has shown that music can be used to educate or disseminate information about public health crises. Grounded in the edutainment approach, we explored how songs are being used to create awareness about COVID-19 in Ghana, a sub-Saharan African country. YouTube was searched, and 28 songs met the study inclusion criteria. We conducted a thematic analysis of the song lyrics. Most lyrics were in English, Ghanaian Pidgin English, Akan, Ga, or Dagbani. Reflecting the multilingual population of Ghana, half of the songs contained three languages to convey their message, and only five songs were in one language. Eight themes emerged from the analysis: public health guidelines, COVID-19 is real and not a hoax, COVID-19 is infectious, prayer as method to stop the virus, emotional reaction and disruption of "everyday" activities; verbally expelling the virus, call for unity and collective efforts, and inspiring hope. We show that songs have the potential as a method for rapidly sharing information about emerging public health crises. Even though, it is beyond the scope of this study to draw conclusions about the reception and impact of songs on awareness and knowledge, the study shows that examining song lyrics can still be useful in understanding local attitudes toward COVID-19, as well as strategies for promoting preventive behaviors. We note that additional multidimensional efforts are needed to increase awareness among the general public about the COVID-19 pandemic.